Associations between anticoagulant treatment pathways and self-reported harms in patients recently diagnosed with venous thromboembolism. Issue 182 (October 2019) - Pan, Steven; Allahwerdy, Fady; Kim, Kibum; Feehan, Michael; Jones, Aubrey E.; Munger, Mark A.; Witt, Daniel M.
Abstract: Introduction: Understanding potential harms associated with common anticoagulation treatment patterns in patients with venous thromboembolism (VTE) is important for multiple stakeholders. The purpose of this study is to report associations between different anticoagulation patterns and bleeding and emotional harms based on patients' self-reported care experiences. Methods: Patients at least 18 years of age who had experienced a VTE event in the past two years and completed a national online survey between May and July 2016 were analyzed. The survey assessed the prevalence of self-reported bleeding and emotional harms associated with self-reported anticoagulation treatment patterns and other variables. Results: Patients mean age was 52.4 (standard deviation 14.4) years and most were female (56.7%) and Caucasian (88.6%). Anticoagulant treatment patterns included warfarin (38.7%), direct oral anticoagulants (26.1%), and those who switched between anticoagulants (17.9%). Self-reported bleeding and emotional harms occurred in 63.6% and 56.3% of patients, respectively. Younger age, experiencing VTE more recently, and a prior history of anxiety, depression, or stroke were associated with increased odds of experiencing bleeding or emotional harm. Compared to warfarin, switching between anticoagulant types was associated with approximately twice the odds of experiencing bleeding harm, while DOAC therapy was associated with lower odds of experiencing emotional harm. Conclusion: Self-reported bleeding and emotional harms occurred commonly during VTE treatment and were associated with identifiable clinical, demographic, and psychosocial characteristics such as younger age, history of depression and/or anxiety, and more recent VTE diagnosis. Switching between anticoagulants may be a marker for increased harm risk. Highlights: Self-reported anticoagulant therapy patterns were associated with risk of experiencingharms during VTE treatment. Pateints Patients who switched between anticoagulantswere approximately twice as likely toexperience a composite harm outcome. Compared to warfarin therapy patients who were prescribed DOACs had reduced odds of reporting emotional harm. Associations were found between various patient characteristics and increased odds of experiencing harm.